Writing Skills in English among School Children Gender Differences, Relationship with Class Performance and with Speaking Skills - Gupta, Raj Kumari; Joshi, Prerna; Gunpal (JOURNAL OF INDIAN EDUCATION, 2015)
Present study focuses on gender differences in writing skills, relationship of writing skills with oral skills and with class performance. A sample of 90 boys and 90 girls from fourth grade were selected to study gender differences. A set of 70 students of seventh grade were assessed for relationship of writing skills with oral skills and with class performance. Writing was assessed on a set of familiar topic and spelling and speaking on seven familiar questions. For class performance, scores of half yearly exams and two unit tests were taken. Girls outperformed boys in writing skills and writing skills were significantly correlated with speaking skills and with class performance.